Method for preparing milk-fiber-modified amino silicon oil anti-pilling softener - MENG HAOYING; LU NA; ZHANG JING (2016)
The invention discloses a method for preparing a milk-fiber-modified amino silicon oil anti-pilling softener, and belongs to the technical field of textile assistants. The method includes the steps that fresh apple juice is subjected to ultrasonic treatment and extraction to obtain a surfactant, and octamethyl cyclotetrasiloxane and a tetramethylammonium hydroxide solution are reacted under the protection of nitrogen to obtain amino silicon oil prepolymers; degreased milk is subjected to impurity removing, drying and dehydration, the dehydrated milk and polyacrylonitrile are crosslinked and polymerized, milk fibers are obtained and reacted with the amino silicon oil prepolymers to obtain milk-fiber-modified amino silicon oil, the milk-fiber-modified amino silicon oil, the surfactant and various enzymes are stirred and mixed, and the milk-fiber-modified amino silicon oil anti-pilling softener is prepared. According to the method, due to the knitted fabric flexibility generated by the milk fibers and the amino